GRPR-Antagonists Carrying DOTAGA-Chelator via Positively Charged Linkers: Perspectives for Prostate Cancer Theranostics - Karim Obeid; Panagiotis Kanellopoulos; Ayman Abouzayed; Adam Mattsson; Vladimir Tolmachev; Berthold A. Nock; Theodosia Maina; Anna Orlova (MDPI AG, 2024)
Gastrin-releasing peptide receptor (GRPR)-antagonists have served as motifs in the development of theranostic radioligands for prostate cancer. Our efforts have been focused on the development of radiolabeled RM26 (H-DPhe6-Gln7-Trp8-Ala9-Val10-Gly11-His12-Sta13-Leu14-NH2) analogs, such as [111In]In-DOTAGA-PEG2-RM26. We recently showed that its Gly11/Sar11-substituted version, [111In]In-AU-RM26-M1, resisted degradation by neprilysin (NEP) while in circulation and achieved higher tumor uptake in mice. We herein introduce the following three new AU-RM26-M1 mimics labeled with In-111, with basic residues in the linker: (i) AU-RM26-M2 (PEG2-Pip), (ii) AU-RM26-M3 (PEG2-Arg), and (iii) AU-RM26-M4 (Arg-Arg-Pip). These analogs were compared in PC-3 cells and animal models vs. AU-RM26-M1 (reference). The new analogs showed high affinity and specificity for the GRPR, exhibiting an uptake and distribution pattern in PC-3 cells typical for a radiolabeled GRPR-antagonist. They showed high stability in peripheral mice blood, except for [111In]In-AU-RM26-M3. AU-RM26-M4 achieved the highest tumor uptake and promising background clearance, followed by [111In]In-RM26-M2, showing lower background levels. These findings were confirmed for [111In]In-AU-RM26-M2 and [111In]In-AU-RM26-M4 by micro-SPECT/CT at 4 and 24 h post-injection. Hence, the type of positively charged residues in the linker of AU-RM26-M1 mimics strongly influenced biological behavior. The analogs with Pip next to DPhe6 demonstrated the best overall characteristics and warrant further investigation.